Chicken DNA virus sensor DDX41 activates IFN-β signaling pathway dependent on STING. (November 2017) - Cheng, Yuqiang; Liu, Yunxia; Wang, Yingying; Niu, Qiaona; Gao, Quanxin; Fu, Qiang; Ma, Jingjiao; Wang, Hengan; Yan, Yaxian; Ding, Chan; Sun, Jianhe
Abstract: The recognition of pathogenic DNA is important to the initiation of antiviral responses. Here, we report the identification of the first avian DEAD (Asp-Glu-Ala-Asp) box polypeptide 41 (DDX41), an important DNA sensor, in chicken cells. In our study, we confirmed that chDDX41 is not an interferon-inducible gene. Knockdown of chDDX41 expression by shRNA blocked the ability of DF-1 cells to mount an IFN-β response to DNA and associated viruses. ChDDX41 mRNAs could be upregulated by double-stranded DNA (dsDNA) analogue poly(dA:dT), but not by double-stranded RNA (dsRNA) analogue poly(I:C). In poly(dA:dT) stimulation assays, the immune molecules involved in the DDX41-mediated IFN-β pathway in human cells were universally upregulated in chicken cells. Via coimmunoprecipitation (Co-IP) experiments, we found that chDDX41 could strongly interact with chicken stimulator of IFN genes (chSTING). Therefore, our results suggest that chDDX41 is involved in the dsDNA- and dsDNA virus-mediated chDDX41-chSTING-IFN-β signaling pathway in chicken cells. Highlights: The first avian DDX41 (chDDX41) was identified from chicken cells. ChDDX41 is involved in the dsDNA- and dsDNA virus-mediated IFN-β signaling. ChDDX41 interacts with chSTING to construct a chDDX41-chSTING-IFN-β pathway.